Virus-Like Particles Containing the Tetrameric Ectodomain of Influenza Matrix Protein 2 and Flagellin Induce Heterosubtypic Protection in Mice - Li Wang (BioMed Research International, 2013)
The ectodomain of matrix protein 2 (M2e) is highly conserved among influenza A viruses and can be a promising candidate antigen for a broadly cross-protective vaccine. In this study, a tetrameric M2e (tM2e) and a truncated form of flagellin (tFliC) were coincorporated into virus-like particles (VLPs) to enhance its immunogenicity. Our data showed that the majority of M2e in VLPs was presented as tetramers by introducing a foreign tetramerization motif GCN4. Intranasal immunization with tM2e VLPs significantly enhanced the levels of serum IgG and IgG subclasses compared to soluble M2e (sM2e) in mice. tM2e VLPs also induced higher M2e-specific T-cell and mucosal antibody responses, conferring complete protection against homologous influenza virus infection. The immunogenicity of tM2e VLPs was further enhanced by coincorporation of the membrane-anchored tFliC (tM2e chimeric VLPs) or coadministration with tFliC VLPs as a mixture, but not the soluble flagellin, inducing strong humoral and cellular immune responses conferring cross-protection against lethal challenge with heterotypic influenza viruses. These results support the development of tM2e chimeric VLPs as universal vaccines and warrant further investigation.